Strategy insight: Mechanical properties of biomaterials’ influence on hydrogel-mesenchymal stromal cell combination for osteoarthritis therapy - Ying, Haoli; Shen, Chengchun; Pan, Ruolang; Li, Xiongfeng; Chen, Ye (Frontiers in Pharmacology, 2023)
Osteoarthritis (OA) is a kind of degenerative joint disease usually found in older adults and those who have received meniscal surgery, bringing great suffering to a number of patients worldwide. One of the major pathological features of OA is retrograde changes in the articular cartilage. Mesenchymal stromal cells (MSCs) can differentiate into chondrocytes and promote cartilage regeneration, thus having great potential for the treatment of osteoarthritis. However, improving the therapeutic effect of MSCs in the joint cavity is still an open problem. Hydrogel made of different biomaterials has been recognized as an ideal carrier for MSCs in recent years. This review focuses on the influence of the mechanical properties of hydrogels on the efficacy of MSCs in OA treatment and compares artificial materials with articular cartilage, hoping to provide a reference for further development of modified hydrogels to improve the therapeutic effect of MSCs.